A study on the use of a metadata schema for characterizing school education STEM lessons plans by STEM teachers - Zervas, P.; Tsourlidaki, E.; Cao, Y.; Sotiriou, S.; Sampson, Demetrios; Faltin, N. (2016)
© 2016, Springer Science+Business Media New York. Online labs (OLs) constitute digital educational tools which can have a significant role in supporting science, technology, engineering and mathematics (STEM) teachers in their daily teaching practice. Designing STEM lessons supported by specific OLs is a challenging task and thus, it is useful for STEM teachers to be able to share their lesson plans in a way that these can be effectively searched by others. The most common way to facilitate this process is (a) to characterize the lesson plans with appropriately selected educational metadata and (b) to build a web repository that collects the metadata records of the lesson plans (following a common metadata schema) and offers search and retrieval functionalities. In our previous work, a metadata schema that can be used for characterizing STEM lesson plans supported by OLs has been proposed. The scope of this paper is to complement the findings of our previous work and present the technical implementation of the proposed metadata schema via a web-based repository, namely the Go-Lab repository and a study on the real usage of the metadata schema’s elements through the analysis of the lesson plans’ metadata records that have been published to this repository by STEM teachers.